Makna Prasangka sebagai 'Monster' dalam Film Monster (2023) - Meliana, Agdelia; Salman, Doddy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Film is a medium in mass communication that functions to convey messages to audiences through audio-visual forms. This study aims to analyze the meaning of prejudice as a ‘monster’ in the Japanese film Monster (2023) using Roland Barthes’ semiotic analysis and Edwin M. Lemert’s labeling theory. The focus of this research is on visual and narrative signs that indicate social prejudice toward the Other within the context of social relations in Japanese society. The main concepts employed include mass communication, film as a medium of mass communication, prejudice, the concept of monsters in Japanese culture, Roland Barthes semiotics, and labeling theory. This study adopts a qualitative approach with semiotic text analysis to examine denotative, connotative, and mythic meanings presented in the film. The findings show that the ‘monster’ in the film does not refer to a physical being, but rather to a social construct formed through rigid cultural systems and social institutions. Labeling mechanisms, normative pressures, and Japanese cultural values play an important role in transforming difference into stigma. Thus, Monster conveys a social critique of society’s efforts to maintain superficial harmony by excluding individuals who are considered different. The film essentially addresses the failure of social systems to protect individuals. Prejudice and the labeling of